2006
DOI: 10.1111/j.1939-1676.2006.tb00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Intravascular Coagulation in Cats

Abstract: The purpose of this study was to describe the clinical characteristics of cats with disseminated intravascular coagulation (DIC), including associated diseases and hemostatic abnormalities, and to identify risk factors for death and treatments that potentially altered outcome. Medical records for cats with DIC from 1990-2004 were evaluated retrospectively. Inclusion criteria were the presence of an underlying disorder associated with DIC and either postmortem examination findings of intravascular fibrin deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 14 publications
2
41
1
Order By: Relevance
“…The bleeding is caused by either inactivation or excess consumption of platelets and/or clotting factors because of increased fibrinolysis and may have a gradual or acute onset. Once this process starts, changes in the patient’s status occur rapidly and require intense monitoring with subsequent changes in therapy as indicated [2]. The classic cutaneous manifestations of DIC present as skin wounds such as bruising, contusions, petechiae, purpura, acral cyanosis, hemorrhagic bullae, purpura fulminans, subcutaneous dissecting hematomata, or bleeding from wound or venipuncture sites [3].…”
Section: Introductionmentioning
confidence: 99%
“…The bleeding is caused by either inactivation or excess consumption of platelets and/or clotting factors because of increased fibrinolysis and may have a gradual or acute onset. Once this process starts, changes in the patient’s status occur rapidly and require intense monitoring with subsequent changes in therapy as indicated [2]. The classic cutaneous manifestations of DIC present as skin wounds such as bruising, contusions, petechiae, purpura, acral cyanosis, hemorrhagic bullae, purpura fulminans, subcutaneous dissecting hematomata, or bleeding from wound or venipuncture sites [3].…”
Section: Introductionmentioning
confidence: 99%
“…[144][145][146] Clinical signs vary considerably and range from asymptomatic (nonovert DIC) to signs of organ failure associated with microvascular thrombosis to fulminant bleeding (overt DIC). 148 Bleeding tendencies reflect disorders of primary and/or secondary hemostasis and may manifest as prolonged bleeding from venipuncture sites, ecchymoses, epistaxis, hematoma formation, and/or gastrointestinal, urinary, or intracavitary hemorrhage. Hemostatic evaluation via TEG showed that the majority of dogs with DIC were hypercoagulable; only 22% were hypocoagulable.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 99%
“…1,19,148,149 The International Society on Thrombosis and Hemostasis (ISTH) recommends a diagnostic scoring algorithm for human patients. DIC represents a dynamic continuum, and findings depend on where that patient lies on the continuum at that point in time.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 99%
“…DIC in the cat has been associated with neoplasia, pancreatitis and infection, with or without sepsis, and it carries a poor prognosis, with only 7% of cats surviving in one study (16). Inhibitors of these systems are consumed and microthrombus formation causes end organ damage.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 99%